2016
DOI: 10.1038/srep35945
|View full text |Cite
|
Sign up to set email alerts
|

System analysis of gene mutations and clinical phenotype in Chinese patients with autosomal-dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disorder mainly caused by mutation in PKD1/PKD2. However, ethnic differences in mutations, the association between mutation genotype/clinical phenotype, and the clinical applicable value of mutation detection are poorly understood. We made systematically analysis of Chinese ADPKD patients based on a next-generation sequencing platform. Among 148 ADPKD patients enrolled, 108 mutations were detected in 127 patients (85.8%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Definite pathogenic mutations accounted for 69.9% of all identified mutations in the present study, which was comparable to the results from the previously reported 45.1–66.6% in Caucasian populations [8, 17, 31], but higher than the 27.7–52.2% reported in Asian populations [25, 32]. Among the definite pathogenic mutations, the large deletion mutation was a special one that was detected by MLPA analysis [15].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Definite pathogenic mutations accounted for 69.9% of all identified mutations in the present study, which was comparable to the results from the previously reported 45.1–66.6% in Caucasian populations [8, 17, 31], but higher than the 27.7–52.2% reported in Asian populations [25, 32]. Among the definite pathogenic mutations, the large deletion mutation was a special one that was detected by MLPA analysis [15].…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, the overall detection rate of PKD mutations was 81.7%, which was consistent with the range of 52.3–85.8% reported in previous studies among Chinese populations [21-25]. Neither PKD1 nor PKD2 mutations were found in 22 probands with a clinical manifestation of ADPKD.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…With the development of genetic testing technology, it is possible to make a definitive diagnosis before the onset age of a patient. Genotypes can also provide the basis for disease progression and prognosis (Jin et al, ). Based on our research and clinical experience, we designed the diagnosis process for patients with a positive family history (Figure ).…”
Section: Discussionmentioning
confidence: 99%